Resin-coated wavelength conversion particles and photocurable ink composition
Coating quantum dots or organic phosphors with a translucent resin and alicyclic epoxy compound in photocurable ink compositions addresses deterioration issues, ensuring effective wavelength conversion and rapid curing.
Patent Information
- Application Number
- JP2021081837
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-05-13
- Publication Date
- 2025-01-08
- Estimated Expiration
- 2041-05-13
AI Technical Summary
Existing photocurable ink compositions using quantum dots or organic phosphors face issues with deterioration due to chemicals and acids, leading to degraded wavelength conversion characteristics, and direct coating with epoxy resin exacerbates this problem.
Coating wavelength conversion particles with a translucent resin and a cured alicyclic epoxy compound, which enhances water resistance and gas barrier properties, protecting the particles from acid generators and maintaining their wavelength conversion characteristics.
The resin-coated wavelength conversion particles maintain their properties effectively in photocurable ink compositions, with improved durability and rapid photocuring capabilities.
Smart Images

Figure 0007610219000001 
Figure 0007610219000002 
Figure 0007610219000003
Abstract
Description
[Technical field]
[0001] The present invention relates to resin-coated wavelength conversion particles in which wavelength conversion particles such as quantum dots are coated with a resin, a photocurable ink composition using the same, and a method for producing resin-coated wavelength conversion particles. [Background technology]
[0002] In recent years, in the market for flat panel displays such as liquid crystal displays (LCDs), there has been an increasing demand for improved color reproducibility in image display. In this regard, quantum dots (QDs) have been attracting attention as a light-emitting material. For example, when excitation light from a backlight is incident on a wavelength conversion member containing quantum dots, the quantum dots are excited and emit fluorescence. By using quantum dots with different emission characteristics, red light, green light, and blue light can be emitted. The fluorescence from quantum dots has a small half-width, and therefore has excellent reproducibility.
[0003] Patent Document 1 proposes a quantum dot-containing polymerizable composition for forming such a wavelength conversion film, in which quantum dots are dispersed in an organic matrix containing a polymer made of (meth)acrylate monomers or the like and a phosphite triester.
[0004] However, when using quantum dots, etc., if a gas barrier layer is not provided, the quantum dots will deteriorate due to water and oxygen, resulting in low durability. For this reason, it is necessary to sandwich the quantum dots between glass and seal the ends, which leads to increased costs, weight, and lack of flexibility.
[0005] In addition to such display applications, ink compositions containing quantum dots are also known. For example, as a photocurable ink composition containing quantum dots, a photocurable ink composition has been proposed in which a ligand is bonded to quantum dots and the quantum dots are dispersed in a UV-curable resin containing an epoxy resin, as in Patent Document 2.
[0006] Furthermore, as a technique for using a resin-coated fluorescent pigment, for example, Patent Document 3 has proposed a photocurable ink composition in which a pigment such as a fluorescent substance is coated with a resin such as an epoxy resin and the like, and the coated pigment is dispersed in a cationic polymerizable compound. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2017-62458 A [Patent Document 2] Special Publication No. 2021-501230 [Patent Document 3] JP 2005-132874 A Summary of the Invention [Problem to be solved by the invention]
[0008] However, as in Patent Documents 1 and 2, when quantum dots or organic phosphors are dispersed directly in a photocurable ink composition without being coated, the quantum dots and the like are deteriorated by acidic groups contained in the composition, and radicals and acids generated during polymerization, resulting in a problem of reduced wavelength conversion characteristics.
[0009] Furthermore, according to the inventors' investigations, it was found that when quantum dots or the like are directly coated with epoxy resin as in Patent Document 3, the quantum dots or the like are deteriorated by the acid generator or the like used together with the epoxy resin, and the wavelength conversion characteristics of the resulting printed matter are reduced.
[0010] Therefore, an object of the present invention is to provide resin-coated wavelength-converting particles, a photocurable ink composition using the same, and a method for producing resin-coated wavelength-converting particles, which are capable of favorably maintaining the wavelength conversion characteristics of the wavelength-converting particles even when wavelength-converting particles such as quantum dots are used in a photocurable ink composition. [Means for solving the problem]
[0011] The present inventors conducted intensive research in order to achieve the above object and discovered that by coating wavelength-converting particles with a first coating material containing a light-transmitting resin and a second coating material containing a cured product of an alicyclic epoxy compound, the wavelength-converting properties of the wavelength-converting particles can be favorably maintained even when used in a photocurable ink composition, thereby completing the present invention.
[0012] That is, the present invention includes the following.
[0013] [1] A resin-coated wavelength-converting particle comprising: a wavelength-converting particle containing a quantum dot or an organic phosphor; a first coating material coating the wavelength-converting particle and containing a light-transmitting resin; and a second coating material coating the first coating material and containing a cured product of an alicyclic epoxy compound.
[0014] [2] The resin-coated wavelength conversion particle according to [1], wherein the alicyclic epoxy compound comprises one or more aliphatic rings and one or more oxygen atoms directly bonded thereto.
[0015] [3] The resin-coated wavelength conversion particle according to [1] or [2], wherein the light-transmitting resin is a (meth)acrylic resin, a polycarbonate resin, a polystyrene resin, or a polyolefin resin.
[0016] [4] The resin-coated wavelength-converting particle according to any one of [1] to [3], wherein the wavelength-converting particle has an emission wavelength in the range of 500 to 580 nm or 600 to 680 nm.
[0017] [5] A photocurable ink composition comprising the resin-coated wavelength conversion particle according to any one of [1] to [4], a radically polymerizable compound, and a photopolymerization initiator.
[0018] [6] A method for producing resin-coated wavelength-converting particles, the method comprising the step of spraying, under light irradiation, a dispersion comprising first coated particles in which wavelength-converting particles containing quantum dots or organic phosphors are coated with a first coating material containing a light-transmitting resin, an alicyclic epoxy compound, and a photoacid generator, to obtain resin-coated wavelength-converting particles in which the alicyclic epoxy compound is cured. Effect of the Invention
[0019] According to the resin-coated wavelength-converting particles of the present invention, even when wavelength-converting particles such as quantum dots are used in a photocurable ink composition, the wavelength-converting properties of the wavelength-converting particles can be favorably maintained. Although the details of the reason are not clear, it is believed that the water resistance and gas barrier properties are particularly enhanced by providing a second coating material containing a cured product of an alicyclic epoxy compound on the wavelength-converting particles, thereby suppressing deterioration of the wavelength-converting particles. It is also believed that the deterioration of the quantum dots, etc., caused by the acid generator, etc. used together with the alicyclic epoxy compound, can be suppressed by providing a first coating material containing a light-transmitting resin in advance.
[0020] Furthermore, the photocurable ink composition of the present invention contains resin-coated wavelength-converting particles that provide such effects, a radically polymerizable compound, and a photopolymerization initiator, and therefore even when used in a photocurable ink composition, the wavelength converting properties of the wavelength-converting particles can be favorably maintained, and the ink can be rapidly cured by photocuring.
[0021] Furthermore, the method for producing resin-coated wavelength conversion particles of the present invention includes a step of spraying a dispersion containing first coated particles, an alicyclic epoxy compound, and a photoacid generator under light irradiation to obtain resin-coated wavelength conversion particles in which the alicyclic epoxy compound is cured, and therefore it is possible to continuously and stably produce resin-coated wavelength conversion particles as fine particles having a relatively uniform particle size. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] <Resin-coated wavelength conversion particles> The resin-coated wavelength-converting particle of the present invention comprises a wavelength-converting particle, a first coating material that coats the wavelength-converting particle, and a second coating material that coats the first coating material. A particle in which the wavelength-converting particle is coated with the first coating material (hereinafter referred to as the "first coated particle") may contain one or more wavelength-converting particles. A particle coated with the second coating material (hereinafter sometimes referred to as the "second coated particle") (i.e., in the resin-coated wavelength-converting particle) may contain one or more first coated particles.
[0023] In this specification, "coating" refers to a state in which 60% or more of the surface area of the object to be coated is covered, preferably 90% or more, and more preferably 100%. Furthermore, "coating" is a concept that includes not only cases in which particles are covered in layers, but also cases in which particles are dispersed in a base material.
[0024] The resin-coated wavelength conversion particles may have any shape, but are preferably spherical, elliptical, etc., from the viewpoint of suitability for addition to ink, etc. to form a fine pattern. Similarly, the first coated particles may have any shape, but are preferably spherical, elliptical, etc., from the viewpoint of suitability for addition to ink, etc. to form a fine pattern.
[0025] A preferred particle structure of the resin-coated wavelength-converting particles is one in which a plurality of wavelength-converting particles are dispersed in a particulate first coating material, and a single first coated particle is covered in a layer of the second coating material, or a single wavelength-converting particle is covered in a layer of the first coating material, and a single first coated particle is covered in a layer of the second coating material.
[0026] The average particle size of the second coated particles (resin-coated wavelength conversion particles) (volume-based D 50 ) is preferably 9 to 300 nm, more preferably 90 to 150 nm, from the viewpoint of ensuring chemical resistance and gas barrier performance while being suitable for forming a fine pattern when added to an ink or the like.
[0027] The average particle size of the first coated particle (volume-based D 50 From the viewpoint of obtaining sufficient emission intensity while ensuring the thickness of the second coating material, the thickness is preferably 20 to 50 nm, and more preferably 20 to 30 nm.
[0028] In the resin-coated wavelength-converting particles, the wavelength-converting particles contain quantum dots or organic phosphors, the first coating material contains a light-transmitting resin, and the second coating material contains a cured product of an alicyclic epoxy compound. Each material will be described below.
[0029] [Wavelength conversion particles] The wavelength conversion particles contain one or more of quantum dots or organic phosphors, and the resin-coated wavelength conversion particles contain these and thereby have a wavelength conversion function.
[0030] The wavelength conversion characteristics of the quantum dots or organic phosphors are not particularly limited, but the wavelength conversion characteristics of the resin-coated wavelength conversion particles are such that, for blue excitation light with a wavelength of 400 nm to 480 nm, preferably 440 to 470 nm, when red light is emitted, the emission wavelength (peak wavelength) is preferably 600 to 680 nm, more preferably 610 to 640 nm, and when green light is emitted, the emission wavelength (peak wavelength) is preferably 500 to 580 nm, more preferably 520 to 560 nm.
[0031] (Quantum dots) Quantum dots refer to nanoscale particles with unique optical properties according to quantum chemistry and quantum mechanics, and since the optical properties can be adjusted by the particle size, they have characteristic light emission properties that depend on the particle size. In the present invention, semiconductor quantum dots, carbon quantum dots, silicon quantum dots, perovskite quantum dots, etc. can be used depending on the emission wavelength of the converted light. In addition, by using multiple quantum dots selected from these and adjusting the content of each, a desired emission wavelength can be obtained.
[0032] The content of the quantum dots in the resin-coated wavelength conversion particles is preferably 1 to 10 mass %, more preferably 2 to 6 mass %, from the viewpoint of obtaining sufficient luminous intensity while ensuring the thickness and amount of the coating material.
[0033] (Carbon-based quantum dots) Carbon-based quantum dots have luminescence properties that depend on particle size due to π bonds between carbon atoms. Examples of carbon-based quantum dots include graphene quantum dots having a graphene structure, carbon quantum dots not having a graphene structure, and quantum dots obtained by chemically modifying these, among which graphene quantum dots or chemically modified graphene quantum dots are preferred from the viewpoint of quantum yield.
[0034] These carbon-based quantum dots are commercially available from Sigma-Aldrich Corporation, Fuji Pigment Co., Ltd., GS Alliance Co., Ltd., Funakoshi Co., Ltd., Kishida Chemical Co., Ltd., and the like, and any of these can be used.
[0035] (Graphene quantum dots) Graphene quantum dots include non-functionalized graphene quantum dots, functionalized graphene quantum dots, pristine graphene quantum dots, and combinations thereof.
[0036] The functionalized graphene quantum dots may be functionalized with one or more functional groups, including oxygen groups, carboxyl groups, carbonyl groups, amorphous carbon, hydroxyl groups, alkyl groups, aryl groups, esters, amines, amides, polymers, poly(propylene oxide), and combinations thereof.
[0037] The graphene quantum dots also include functionalized graphene quantum dots that are functionalized with one or more alkyl groups. The alkyl groups include methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, and combinations thereof. In some embodiments, the alkyl groups include octyl groups (e.g., octylamine).
[0038] The graphene quantum dots can also be functionalized with one or more polymer precursors, for example, the graphene quantum dots can be functionalized with one or more monomers (e.g., vinyl monomers).
[0039] Graphene quantum dots can be functionalized with a polymer precursor that is polymerized to form polymer-functionalized graphene quantum dots, for example, end-functionalized with a vinyl monomer that is polymerized to form an end-functionalized polyvinyl adduct.
[0040] The graphene quantum dots include functionalized graphene quantum dots that are functionalized with one or more hydrophilic functional groups, including carboxyl groups, carbonyl groups, hydroxyl groups, hydroxyalkyl groups, poly(ethylene glycol), poly(vinyl alcohol), poly(acrylic acid), and combinations thereof.
[0041] The graphene quantum dots include functionalized graphene quantum dots that are functionalized with one or more hydrophobic functional groups. The hydrophobic functional groups include alkyl groups, aryl groups, and combinations thereof. The hydrophobic functional groups include one or more alkylamides or arylamides.
[0042] The graphene quantum dots include edge-functionalized graphene quantum dots. The edge-functionalized graphene quantum dots include one or more hydrophobic functional groups as described above. The edge-functionalized graphene quantum dots include one or more hydrophobic functional groups as described above. The edge-functionalized graphene quantum dots include one or more hydrophilic functional groups, also as described above. The edge-functionalized graphene quantum dots include one or more oxygen appendages on their edges. The edge-functionalized graphene quantum dots include one or more amorphous carbon appendages on their edges.
[0043] The graphene quantum dots are end-functionalized with one or more alkyl or aryl groups, such as alkylamides or arylamides. The end-functionalization of the graphene quantum dots with alkyl or aryl groups is accomplished by reaction of the alkylamides or arylamides at the ends of the graphene quantum dots with carboxylic acids.
[0044] Graphene quantum dots include pristine graphene quantum dots. Pristine graphene quantum dots include graphene quantum dots that are untreated after synthesis. Pristine graphene quantum dots include graphene quantum dots that have not undergone any additional surface modification after synthesis.
[0045] Graphene quantum dots can be obtained from a variety of sources. For example, graphene quantum dots include coal-derived graphene quantum dots, coke-derived graphene quantum dots, and combinations thereof. Graphene quantum dots include coke-derived graphene quantum dots. Graphene quantum dots include coal-derived graphene quantum dots. Coal includes (but is not limited to) anthracite, bituminous coal, subbituminous coal, modified bituminous coal, asphaltenes, asphalt, peat, lignite, boiler coal, petrified oil, carbon black, activated carbon, and combinations thereof. The carbon source is bituminous coal. The carbon includes bituminous coal.
[0046] The graphene quantum dots can have a variety of diameters, for example, the graphene quantum dots preferably have a diameter ranging from about 1 nm to about 100 nm, more preferably from about 1 nm to about 50 nm, and even more preferably from about 1 nm to about 20 nm.
[0047] Graphene quantum dots can also have a variety of structures. For example, the graphene quantum dots can have a crystalline structure, such as a crystalline hexagonal structure. The graphene quantum dots can have a single layer or multiple layers, such as a graphene quantum dot having about two layers to about four layers.
[0048] The graphene quantum dots may have various quantum yields. The graphene quantum dots preferably have a quantum yield in the range of about 30 to 80%. In addition, the fluorescent properties of the graphene quantum dots in an aqueous dispersion are preferably such that the emission wavelength is 380 nm to 650 nm with respect to at least any one of the wavelengths of the excitation light of 300 nm to 420 nm.
[0049] The graphene quantum dots may be in the form of a powder or pellets, or in the form of a liquid, dispersion, solution, or melt.
[0050] Various methods can be used to form graphene quantum dots. For example, the step of forming graphene quantum dots can include exposing a carbon source to an oxidizing agent, thereby forming the graphene quantum dots. Carbon sources include coal, coke, and combinations thereof.
[0051] The oxidizers include acids, including sulfuric acid, nitric acid, phosphoric acid, hypophosphorous acid, oleum, hydrochloric acid, oleum, chlorosulfonic acid, and combinations thereof. The oxidizers also include potassium permanganate, sodium permanganate, hypophosphorous acid, nitric acid, sulfuric acid, hydrogen peroxide, and combinations thereof. A preferred oxidizer is a mixture of potassium permanganate, sulfuric acid, and hypophosphorous acid.
[0052] The carbon source is exposed to the oxidizing agent by sonicating the carbon source in the presence of the oxidizing agent. Heating the carbon source in the presence of the oxidizing agent is included. Heating is at a temperature of at least about 100°C.
[0053] The use of further methods for forming graphene quantum dots can also be envisaged. For example, further methods for forming graphene quantum dots are disclosed in International Patent Application PCT / US2014 / 036604. Further suitable methods for producing graphene quantum dots are also disclosed in the following references: ACS Appl. Mater. Interfaces 2015, 7, 7041-7048; and Nature Commun. 2013, 4:2943, 1-6.
[0054] (Carbon quantum dots) Carbon quantum dots are quantum dots that do not have a ring structure like graphene. They are more susceptible to the effects of pH than graphene quantum dots, and have the property of changing the emission intensity and peak position.
[0055] The carbon quantum dots can have a variety of diameters, for example, the carbon quantum dots preferably have a diameter ranging from about 1 nm to about 100 nm, more preferably from about 1 nm to about 50 nm, and even more preferably from about 1 nm to about 30 nm.
[0056] Carbon quantum dots can also have various quantum yields. Carbon quantum dots preferably have a quantum yield in the range of about 20 to 50%. In addition, the fluorescent properties of the carbon quantum dots in an aqueous dispersion are preferably such that the emission wavelength is 380 nm to 600 nm with respect to at least any one of the wavelengths of excitation light of 300 nm to 420 nm.
[0057] The manufacturing method of carbon quantum dots is not very different from the manufacturing method of graphene quantum dots; the only difference is whether the raw materials used and the manufacturing conditions are favorable for forming a graphene structure.
[0058] Therefore, carbon-based quantum dots including both of them can be produced by, for example, a method of producing them by laser ablation of a carbon target followed by chemical treatment (JP Patent Publication No. 2012-501863), a method of producing them from candle soot (H. Liu, et al., Angew. Chem. Int. Ed. 2007, 46, 6473-6475.), a method of producing them by chemical treatment of graphite oxide (G. Eda, et al., Adv. Mater. 2010, 22, 505-509.), a method of producing them from a chemical reaction using graphite oxide as a precursor (JP Patent Publication No. 2012-136566), a method of producing them from a conversion reaction of fullerene (J. Lu, et al., Nature Nanotech. 2011, 6, 247-252.), or by chemically processing cheaper carbon raw materials such as carbon fiber and activated carbon (J. Peng, et al., Nano Lett. 2012, 12, 844-849.; ZA Qiao, ChemCommun. 2010, 46,8812-8814.; Y. Dong, et al., Chem. Mater.2010, 22, 5895-5899.).
[0059] Although these methods are broadly classified as top-down methods, carbon quantum dots can also be produced by a bottom-up method (GA Ozin, et al., J. Mater. Chem., 2012, 22, 1265-1269.), which produces carbon quantum dots by polymerizing organic precursor molecules.
[0060] Alternatively, carbon quantum dots can be produced by a method for producing carbon quantum dots (JP 2014-133685 A) that includes the steps of mixing a carbon material with hydrogen peroxide, causing a decomposition reaction of carbon with the hydrogen peroxide to prepare a carbon quantum dot production liquid, and separating the carbon quantum dots and the hydrogen peroxide in the carbon quantum dot production liquid to stop the decomposition reaction and obtain the carbon quantum dots.
[0061] (Wavelength conversion properties of carbon-based quantum dots) When carbon-based quantum dots are used, the wavelength conversion characteristics (fluorescence characteristics) are such that, from the viewpoint of making the material a highly versatile fluorescent material, the emission wavelength (peak wavelength) is preferably 400nm to 750nm, more preferably 450nm to 650nm, and even more preferably 500nm to 600nm, for at least any wavelength of excitation light between 300nm and 470nm. Such emission wavelengths are in almost the same range as those of single crystal YAG·Ce.
[0062] Furthermore, the half width of the emission centered on the emission peak wavelength is preferably 40 nm to 100 nm, the emission wavelength is more preferably 400 nm to 700 nm, and the emission wavelength is further preferably 420 nm to 750 nm.
[0063] From the viewpoint of obtaining such fluorescent properties, the fluorescent properties of the aqueous dispersion of carbon-based quantum dots as the raw material are preferably an emission wavelength (peak wavelength) of 380 nm to 600 nm, more preferably an emission wavelength of 400 nm to 550 nm, and even more preferably an emission wavelength of 420 nm to 500 nm, for at least any wavelength of excitation light of 300 nm to 420 nm.
[0064] The quantum yield (luminous efficiency) of the phosphor composition is preferably 25% or more, more preferably 50% or more, and particularly preferably 70 to 80%.
[0065] (Silicon Quantum Dots) When semiconductors are made into nanoparticles, the band structure changes due to the quantum size effect (confinement effect), and they emit fluorescence of a color that corresponds to the particle size. Silicon quantum dots are a typical example of quantum dots made of group IV semiconductors.
[0066] A typical method for synthesizing silicon quantum dots is etching of silicon wafers. Nanoparticles can be obtained by micronizing bulk silicon by electrolytic etching using hydrofluoric acid (HF). The particle size of the resulting particles can be controlled by the etching time. Particle synthesis by thermal decomposition of silane (SiH4) is known as a bottom-up synthesis method that can generate a relatively large amount of particles. Si atoms are generated by thermal decomposition of silane, which becomes supersaturated, and particles are generated by nucleation and growth. Since the particles generated in this way are relatively large in size, the particles are then etched with a mixture of hydrofluoric acid (HF) and nitric acid (HNO3) to reduce the particle size to the range where the quantum size effect appears.
[0067] A synthesis method using plasma CVD is also known as a method for synthesizing single-nanometer particles in one step without an etching process. The precursor silicon tetrabromide (SiBr4) is decomposed in an RF plasma field to generate Si atoms, which are then nucleated and grown in a reactor to produce nanoparticles.
[0068] Silicon quantum dots are commercially available from GS Alliance Co., Ltd., Sigma-Aldrich Co., etc., and they can be used. Commercially available silicon quantum dots have sizes ranging from a few angstroms to 10 nm or less, and have a quantum yield of approximately 20 to 30%.
[0069] Silicon quantum dots can be made to emit light at a wavelength that corresponds to the particle diameter, and in the present invention can be used as wavelength conversion particles for obtaining either a green to yellow color or a red color.
[0070] In the resin-coated wavelength conversion particles containing silicon quantum dots, when red light is emitted in response to a wavelength of 400 nm to 470 nm which is blue excitation light, the emission wavelength (peak wavelength) is preferably 610 nm to 640 nm, and more preferably 620 nm to 640 nm, and when green to yellow light is emitted, the emission wavelength (peak wavelength) is preferably 520 nm to 560 nm, and more preferably 530 nm to 550 nm.
[0071] (Perovskite quantum dots) Perovskite quantum dots have a perovskite crystal structure. In general, the perovskite crystal structure is represented by the composition formula ABX3 using ions A, B, and X, with ions A at eight vertices, ions X at the center of six faces, and ions B at the center of the lattice. Since ions B are relatively smaller than ions A, the centers of gravity of positive and negative charges can be separated due to the ease of movement of ions B. In perovskite quantum dots, ions X are preferably halogen atoms (preferably F, Cl, Br, I), ions A are preferably Cs, and ions B are preferably Pb.
[0072] Perovskite quantum dots are represented by the general formula (1): CsPbY a Z b (In the above general formula (1), Y and Z each independently represent F, Cl, Br or I, a and b each independently represent a real number of 0 to 3, and a+b=3.) Also usable is a compound having a composition of CH3NH3PbX3 (X=Cl, Br, I).
[0073] The perovskite quantum dots preferably include at least one type of quantum dot selected from perovskite quantum dots that emit red light. Since the emission color of luminescent nanocrystals such as quantum dots depends on the particle size of the quantum dots and the energy gap of the luminescent nanocrystals, the emission color can be selected by adjusting the type of perovskite quantum dots used and their particle size.
[0074] Commercially available perovskite quantum dots are nanocrystals of perovskite compounds, with typical compositions being CH3NH3PbX3 and CsPbX3 (X = Cl, Br, I). The quantum yield is about 50-80%, and the half-width is about 18nm-39nm.
[0075] In the case of resin-coated wavelength conversion particles containing perovskite quantum dots, when red light is emitted in response to a wavelength of 400 nm to 470 nm which is the excitation light of a blue LED, the emission wavelength (peak wavelength) is preferably 610 nm to 650 nm, and more preferably 615 nm to 635 nm.
[0076] (Semiconductor quantum dots) Semiconductor-based quantum dots include any type of semiconductor, including II-VI, III-V, IV-VI, and Group IV semiconductors. Suitable semiconductor materials include, but are not limited to, Si, Ge, Sn, Se, Te, B, C, P, BN, BP, BAs, AlN, AlP, AlAs, AlSb, GaN, GaP, GaAs, GaSb, InN, InP, InAs, InSb, ZnO, ZnS, ZnSe, ZnTe, CdS, CdSe, CdSeZn, CdTe, HgS, HgSe, HgTe, BeS, BeSe, BeTe, MgS, MgSe, GeS, GeSe, GeTe, SnS, SnSe, SnTe, PbO, PbS, PbSe, PbTe, CuF, CuCl, CuBr, CuI, Si3N4, Ge3N4, Al2O3, Al2CO, and combinations thereof.
[0077] Semiconductor quantum dots having a core-shell structure can also be used, in which case the core material is preferably a III-V group nanocrystal selected from the group consisting of BN, BP, BAs, BSb, AlN, AlP, AlAs, AlSb, GaN, GaP, GaAs, GaSb, InN, InP, InAs, and InSb.
[0078] Shell materials include Si, Ge, Sn, Se, Te, B, C, P, Co, Au, BN, BP, BAs, AlN, AlP, AlAs, AlSb, GaN, GaP, GaAs, GaSb, InN, InP, InAs, InSb, GaSb, ZnO, ZnS, ZnSe, ZnTe, CdS, CdSe, CdSeZn, CdTe, HgS, HgSe, HgTe, BeS, BeSe, BeTe, MgS, MgSe, GeS, GeSe, GeTe, SnS, SnSe, SnTe, PbO, PbS, PbSe, PbTe, CuF, CuCl, CuBr, CuI, Si3N4, Ge3N4, Al2O3, Al2CO, and combinations thereof.
[0079] The core material can also be doped, with dopants including ZnS, ZnSe, ZnTe, CdSe, CdS, CdTe, HgS, HgSe, HgTe, CuInS2, CuInSe2, AlN, AlP, AlAs, GaN, GaP, or GaAs.
[0080] Representative semiconductor quantum dots include ZnS, InP / ZnS, CdS, CdSe, CuInS2 (CIS), CuInSe2, CuInS2 / ZnS, PbS, and AgInS2.
[0081] In the case of semiconductor quantum dots, the emission wavelength can be changed depending on the type, structure, particle size, etc. of the semiconductor. The average particle size of the semiconductor quantum dots preferably used in the present invention is 2 to 10 nm, more preferably 3 to 6 nm.
[0082] (Organic phosphor) Examples of organic fluorescent materials include cyanine dyes such as acridine orange, aminoacridine, quinacrine, anilinonaphthalenesulfonic acid derivatives, anthroyloxystearic acid, auramine O, chlorotetracycline, merocyanine, and 1,1'-dihexyl-2,2'-oxacarbocyanine, dansyl chloride derivatives such as dansylsulfamide, dansylcholine, dansylgalacside, dansyltolidine, and dansyl chloride, diphenylhexatriene, eosin, ε-adenosine, ethidium bromide, fluorescein, formycin, 4-benzoylamido-4'-aminostilbene-2,2'-sulfonic acid, β-naphthyl triphosphate, oxonol dyes, parinaric acid derivatives, perylene, N -phenylnaphthylamine, pyrene, safranine O, fluorescamine, fluorescein isocyanate, 7-chloronitrobenzo-2-oxa-1,3-diazol, dansyl aziridine, 5-(iodoacetamidoethyl)aminonaphthalene-1-sulfonic acid, 5-iodoacetamidofluorescein, N-(1-anilinonaphthyl-4)maleimide, N-(7-dimethyl-4-methylcoumanyl)maleimide, N-(3-pyrene)maleimide, eosin-5-iodoacetamide, fluorescein mercury acetate, 2-(4'-(2''-iodoacetamido))aminonaphthalene-6-sulfonic acid, eosin, rhodamine derivatives, organic electroluminescent dyes, organic electroluminescent polymers and crystals, dendrimers, and the like can be mentioned.
[0083] The organic phosphor may be dispersed or dissolved in the first coating material. When the organic phosphor is dispersed, the average particle size is, for example, about 30 to 50 nm.
[0084] The content of the organic phosphor in the resin-coated wavelength conversion particles is preferably 1 to 10 mass %, more preferably 2 to 6 mass %, from the viewpoint of obtaining sufficient luminous intensity while ensuring the thickness and amount of the coating material.
[0085] [First covering material] The first coating material that coats the wavelength-converting particles contains a light-transmitting resin. By coating the wavelength-converting particles with the first coating material that contains a light-transmitting resin, the effect of the acid required for curing the alicyclic epoxy compound can be suppressed, and deterioration of the wavelength-converting particles can be suppressed.
[0086] The content of the first coating material in the resin-coated wavelength conversion particles is preferably from 10 to 40 mass %, more preferably from 20 to 35 mass %, from the viewpoint of obtaining a sufficient barrier effect while ensuring the thickness and amount of the second coating material.
[0087] (translucent resin) As the light-transmitting resin, any light-transmitting resin can be used, and examples thereof include those containing, as a main component, one or more of vinyl-based polymers and copolymers, (meth)acrylic-based polymers and copolymers, polycarbonates, polyesters, polyamides, polyimides, polyurethanes, amino-based polymers, silicon-containing polymers, sulfur-containing polymers, and fluorine-containing polymers.
[0088] The light-transmitting resin is preferably hydrophobic, and is preferably a (meth)acrylic resin, a polycarbonate resin, a polystyrene resin, or a polyolefin resin.
[0089] The light-transmitting resin may contain additives such as plasticizers, antioxidants, nucleating agents, clarifying agents, light stabilizers, and antistatic agents, as long as the effects of the present invention are not impaired.
[0090] [Second covering material] The second coating material that coats the first coating material (first coated particles) contains a cured product of an alicyclic epoxy compound, and the alicyclic epoxy compound can be cured in the presence of an acid catalyst. When curing in the presence of an acid catalyst, the alicyclic epoxy compound can be cured by adding an initiator such as a photoacid generator to the alicyclic epoxy compound or by adding the alicyclic epoxy compound to an acidic solution. Therefore, the cured product of the alicyclic epoxy compound may contain not only a component derived from the alicyclic epoxy compound, but also a component derived from an initiator such as a photoacid generator.
[0091] When the second coating material contains a cured product of an alicyclic epoxy compound, the water resistance and gas barrier properties of the coating material are particularly enhanced, making it possible to suppress deterioration of the wavelength converting particles.
[0092] The content of the second coating material in the resin-coated wavelength conversion particles is preferably 60 to 85 mass %, and more preferably 70 to 85 mass %, from the viewpoint of obtaining sufficient water resistance and gas barrier properties while maintaining the size and function of the first coated particles.
[0093] (alicyclic epoxy compounds) The alicyclic epoxy compound refers to a compound containing one or more alicyclic epoxy groups in one molecule, but a compound containing two or more is preferred from the viewpoint of reactivity with a cationic catalyst. The alicyclic epoxy compound may be only one type, or may be two or more types with different structures. In the following, the content of the alicyclic epoxy compound refers to the total content when two or more alicyclic epoxy compounds with different structures are used. The alicyclic epoxy compound has better curing properties by light irradiation than the aliphatic epoxy compound. The use of a polymerizable compound with excellent photocuring properties is advantageous not only in improving productivity, but also in that a layer having uniform physical properties can be formed on the light-irradiated side and the non-irradiated side. In addition, epoxy compounds generally tend to have less curing shrinkage when photocured.
[0094] The alicyclic epoxy compound has at least one alicyclic epoxy group. Here, the alicyclic epoxy group refers to a monovalent substituent having a condensed ring of an epoxy ring and a saturated hydrocarbon ring, and is preferably a monovalent substituent having a condensed ring of an epoxy ring and a cycloalkane ring. More preferred alicyclic epoxy compounds include those having one or more of the following structures in which an epoxy ring and a cyclohexane ring are condensed in one molecule.
[0095] [ka]
[0096] The above structure may be contained in two or more per molecule, and preferably one or two per molecule. The above structure may have one or more substituents. Examples of the substituents include an alkyl group (e.g., an alkyl group having 1 to 6 carbon atoms), a hydroxyl group, an alkoxy group (e.g., an alkoxy group having 1 to 6 carbon atoms), a halogen atom (e.g., a fluorine atom, a chlorine atom, a bromine atom), a cyano group, an amino group, a nitro group, an acyl group, and a carboxyl group. The above structure is preferably unsubstituted.
[0097] The alicyclic epoxy compound may have a polymerizable functional group other than the alicyclic epoxy group. The polymerizable functional group refers to a functional group that can cause a polymerization reaction by radical polymerization or cationic polymerization, and an example of the polymerizable functional group is a (meth)acryloyl group.
[0098] Commercially available products that can be suitably used as the alicyclic epoxy compound include CELLOXIDE 2000, CELLOXIDE 2021P, CELLOXIDE 3000, CELLOXIDE 8000, CYCLOMER M100, EPOLEAD GT301, EPOLEAD GT401, 4-vinylcyclohexene dioxide manufactured by Sigma-Aldrich Co., Ltd., D-limonene oxide manufactured by Nippon Terpene Chemical Co., Ltd., and SANSOCYSER E-PS manufactured by New Japan Chemical Co., Ltd. These can be used alone or in combination of two or more kinds.
[0099] Among them, alicyclic epoxy compounds consisting of one or more aliphatic rings and one or more oxygen atoms directly bonded thereto are particularly preferred from the viewpoints of transparency, water resistance, gas barrier properties, light resistance, etc. As such alicyclic epoxy compounds, the following alicyclic epoxy compounds are available as EPOCALIC THI-DE, DE-102, and DE-103 manufactured by ENEOS Corporation, respectively.
[0100] [ka]
[0101] In addition, the alicyclic epoxy compound can also be produced by a known synthesis method. The synthesis method is not limited, but can be synthesized by referring to, for example, Maruzen KK Publishing, Fourth Edition Experimental Chemistry Lecture 20 Organic Synthesis II, 213-, 1992, Ed. by Alfred Hasfner, The chemistry of heterocyclic compounds-Small Ring Heterocycles part 3 Oxiranes, John & Wiley and Sons, An Interscience Publication, New York, 1985, Yoshimura, Adhesive, Vol. 29, No. 12, 32, 1985, Yoshimura, Adhesive, Vol. 30, No. 5, 42, 1986, Yoshimura, Adhesive, Vol. 30, No. 7, 42, 1986, JP-A-11-100378, JP-A-2926262, and other documents.
[0102] In addition to the alicyclic epoxy compound, an oxetane compound can be used in combination. The oxetane compound is not particularly limited as long as it has one or more oxetane structures in one molecule, and may have two or more oxetane structures in one molecule.
[0103] Specific examples of the compound include 2-ethylhexyloxetane (ARON OXT-212, manufactured by Toagosei Co., Ltd.), xylylene bisoxetane (ARON OXT-121, manufactured by Toagosei Co., Ltd.), 3-ethyl-3{[methoxy]methyl}oxetane (ARON OXT-221, manufactured by Toagosei Co., Ltd.), (3-ethyloxetan-3-yl)methyl acrylate (OXE-10, manufactured by Osaka Organic Chemical Industry Co., Ltd.), and (3-ethyloxetan-3-yl)methyl methacrylate (OXE-30, manufactured by Osaka Organic Chemical Industry Co., Ltd.).
[0104] In addition to the alicyclic epoxy compound, a glycidyl type epoxy compound can be used in combination.
[0105] (Photoacid generator) Examples of photoacid generators that generate acid upon irradiation with light include onium salts, diazonium salts, quinone diazide compounds, organic halides, aromatic sulfonate compounds, bisulfone compounds, sulfonyl compounds, sulfonate compounds, sulfonium compounds, sulfamide compounds, iodonium compounds, sulfonyldiazomethane compounds, and mixtures thereof.
[0106] Specific examples of these compounds include triphenylsulfonium triflate, diphenyliodonium triflate, 2,3,4,4-tetrahydroxybenzophenone-4-naphthoquinone diazide sulfonate, 4-N-phenylamino-2-methoxyphenyldiazonium sulfate, 4-N-phenylamino-2-methoxyphenyldiazonium p-ethylphenyl sulfate, 4-N-phenylamino-2-methoxyphenyldiazonium 2-naphthyl sulfate, 4-N-phenylamino-2-methoxyphenyldiazonium phenyl sulfate, 2,5-diethoxy-4-N-4'-methoxyphenylcarbonylphenyldiazonium-3-carboxy-4-hydrogen 2-Methoxy-4-N-phenylphenyldiazonium-3-carboxy-4-hydroxyphenyl sulfate, diphenylsulfonylmethane, diphenylsulfonylmethane, diphenyldisulfone, α-methylbenzoin tosylate, pyrogallol trimesylate, benzoin tosylate, Midori Chemical MPI-103 (CAS.NO.(87709-41-9)), Midori Chemical BDS-105 (CAS.NO.(145612-66-4)), Midori Chemical NDS-103 (CAS.NO.(110098-97-0)), Midori Chemical MDS-203 (CAS.NO.(127855-15-5)), Midori Chemical Pyrogallol tritosylate (CAS.NO.(20032-64-8)), Midori Chemical Co., Ltd. DTS-102 (CAS.NO.(75482-18-7)), Midori Chemical Co., Ltd. DTS-103 (CAS.NO.(71449-78-0)), Midori Chemical Co., Ltd. MDS-103 (CAS.NO.(127279-74-7)), Midori Chemical Co., Ltd. MDS-105 (CAS.NO.(116808- 67-4), Midori Chemical MDS-205 (CAS.NO.(81416-37-7)), Midori Chemical BMS-105 (CAS.NO.(149934-68-9)), Midori Chemical TMS-105 (CAS.NO.(127820-38-6)), Midori Chemical NB-101 (CAS.NO.(20444-09-1)), Midori Chemical NB-201 (CAS.NO.(4450-68-4)), Midori Chemical Co., Ltd. DNB-101 (CAS.NO.(114719-51-6)), Midori Chemical Co., Ltd. DNB-102 (CAS.NO.(131509-55-2)), Midori Chemical Co., Ltd. DNB-103 (CAS.NO.(132898-35-2)), Midori Chemical Co., Ltd. DNB-104 (CAS.NO.(132898 -36-3)), Midori Chemical Co., Ltd. DNB-105 (CAS.NO.(132898-37-4)), Midori Chemical Co., Ltd. DAM-101 (CAS.NO.(1886-74-4)), Midori Chemical Co., Ltd. DAM-102 (CAS.NO.(28343-24-0)), Midori Chemical Co., Ltd. DAM-103 (CAS.NO.(14159-45-6)), Midori DAM-104 (CAS.NO.(130290-80-1), CAS.NO.(130290-82-3)), DAM-201 (CAS.NO.(28322-50-1)), CMS-105, DAM-301 (CAS.No.(138529-81-4)), SI- 105 (CAS. No. (34694-40-7)), Midori Chemical's NDI-105 (CAS. No. (133710-62-0)), Midori Chemical's EPI-105 (CAS. No. (135133-12-9)), Daicel UCB's UVACURE 1591, and Lamberti's ESACURE-1064.
[0107] Among them, it is preferable to use an onium salt as the photoacid generator. Examples of the usable onium salt include diazonium salts, phosphonium salts, and sulfonium salts having a fluoroborate anion, a hexafluoroantimonate anion, a hexafluoroarsenate anion, a trifluoromethanesulfonate anion, a paratoluenesulfonate anion, and a paranitrotoluenesulfonate anion as a counter ion. [Other ingredients] The second coating material may contain a photosensitizer, a polymerization inhibitor, and the like, provided that the effects of the present invention are not impaired.
[0108] [Applications of resin-coated wavelength conversion particles] The resin-coated wavelength conversion particles can be used as printing inks, inkjet inks, paints, processed pigments, functional dyes, dispersions serving as raw materials therefor, pigment components, and the like.
[0109] Resin-coated wavelength conversion particles have acid resistance, oxidation resistance, water resistance, etc., and are therefore suitable for use in photocurable inks, It can be suitably used in water-based inks, water-based paints, etc.
[0110] <Photocurable ink composition> The photocurable ink composition contains the above-mentioned resin-coated wavelength conversion particles, a radically polymerizable compound, and a photopolymerization initiator.
[0111] The content of the resin-coated wavelength-converting particles in the photocurable ink composition is preferably from 5 to 75% by mass, and more preferably from 20 to 75% by mass, from the viewpoint of obtaining sufficient luminescence intensity after printing while ensuring the strength and durability of the printed matter.
[0112] [Radical polymerizable compounds] The radical polymerizable compound is not particularly limited, but from the viewpoint of transparency, adhesion, etc. of the cured coating film after curing, (meth)acrylate compounds such as monofunctional or polyfunctional (meth)acrylate monomers, and their polymers, prepolymers, etc. are preferred. In this specification, the term "(meth)acrylate" is used to mean at least one of acrylate and methacrylate, or either one of them. The same applies to "(meth)acryloyl" and the like.
[0113] Examples of monofunctional (meth)acrylate monomers include acrylic acid, methacrylic acid, and derivatives thereof, more specifically, monomers having one polymerizable unsaturated bond of (meth)acrylic acid ((meth)acryloyl group) in the molecule. Specific examples of these monomers are listed below, but the present invention is not limited thereto.
[0114] Alkyl (meth)acrylates in which the alkyl group has 1 to 30 carbon atoms, such as methyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isononyl (meth)acrylate, n-octyl (meth)acrylate, lauryl (meth)acrylate, and stearyl (meth)acrylate; aralkyl (meth)acrylates in which the aralkyl group has 7 to 20 carbon atoms, such as benzyl (meth)acrylate; and alkoxyalkyl (meth)acrylate, such as butoxyethyl (meth)acrylate. Alkoxyalkyl (meth)acrylates having a prime number of 2 to 30; aminoalkyl (meth)acrylates having a (monoalkyl or dialkyl)aminoalkyl group with a total carbon number of 1 to 20, such as N,N-dimethylaminoethyl (meth)acrylate; polyalkylene glycol alkyl ether (meth)acrylates having an alkylene chain carbon number of 1 to 10 and a terminal alkyl ether carbon number of 1 to 10, such as diethylene glycol ethyl ether (meth)acrylate, triethylene glycol butyl ether (meth)acrylate, tetraethylene glycol monomethyl ether (meth)acrylate, hexaethylene glycol monomethyl ether (meth)acrylate, octaethylene glycol monomethyl ether (meth)acrylate, nonaethylene glycol monomethyl ether (meth)acrylate, dipropylene glycol monomethyl ether (meth)acrylate, heptapropylene glycol monomethyl ether (meth)acrylate, and tetraethylene glycol monoethyl ether (meth)acrylate; hexaethylene glycol phenyl ether (Meth)acrylates of polyalkylene glycol aryl ethers having an alkylene chain of 1 to 30 carbon atoms and a terminal aryl ether of 6 to 20 carbon atoms, such as (meth)acrylates; (meth)acrylates having an alicyclic structure and a total of 4 to 30 carbon atoms, such as cyclohexyl (meth)acrylate, dicyclopentanyl (meth)acrylate, isobornyl (meth)acrylate, and methylene oxide-added cyclodecatriene (meth)acrylate; fluorinated alkyl (meth)acrylates having a total of 4 to 30 carbon atoms, such as heptadecafluorodecyl (meth)acrylate;Examples of the (meth)acrylates include hydroxyl group-containing (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, triethylene glycol mono(meth)acrylate, tetraethylene glycol mono(meth)acrylate, hexaethylene glycol mono(meth)acrylate, octapropylene glycol mono(meth)acrylate, and glycerol mono- or di(meth)acrylate; glycidyl group-containing (meth)acrylates such as glycidyl (meth)acrylate; polyethylene glycol mono(meth)acrylates having an alkylene chain of 1 to 30 carbon atoms such as tetraethylene glycol mono(meth)acrylate, hexaethylene glycol mono(meth)acrylate, and octapropylene glycol mono(meth)acrylate; and (meth)acrylamides such as (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, 2-hydroxyethyl(meth)acrylamide, and acryloylmorpholine. ;
[0115] As the monofunctional (meth)acrylate monomer, it is preferable to use an alkyl (meth)acrylate having 4 to 30 carbon atoms, and it is more preferable to use an alkyl (meth)acrylate having 12 to 22 carbon atoms from the viewpoint of improving the dispersibility of the quantum dots. The more the dispersibility of the quantum dots is improved, the more the amount of light that goes perpendicular to the emission surface from the wavelength conversion layer increases, which is effective in improving the front brightness and front contrast. Specifically, as the monofunctional (meth)acrylate monomer, butyl (meth)acrylate, octyl (meth)acrylate, lauryl (meth)acrylate, oleyl (meth)acrylate, stearyl (meth)acrylate, behenyl (meth)acrylate, butyl (meth)acrylamide, octyl (meth)acrylamide, lauryl (meth)acrylamide, oleyl (meth)acrylamide, stearyl (meth)acrylamide, behenyl (meth)acrylamide, etc. are preferable. Among these, lauryl (meth)acrylate, oleyl (meth)acrylate, and stearyl (meth)acrylate are particularly preferred.
[0116] In addition, as the monofunctional (meth)acrylate compound, from the viewpoints of further reducing the oxygen permeability coefficient of the wavelength conversion layer and improving adhesion to other layers or members, it is also preferable to use a monofunctional (meth)acrylate compound having one or more groups selected from the group consisting of a hydroxyl group and an aryl group.
[0117] The groups contained in the monofunctional (meth)acrylate compound are preferably a hydroxy group or a phenyl group.Specific preferred compounds include benzyl acrylate, phenoxyethyl acrylate, phenoxydiethylene glycol acrylate, 1,4-cyclohexanedimethanol monoacrylate, 2-hydroxy-3-phenoxypropyl acrylate, and 4-hydroxybutyl acrylate.
[0118] A polyfunctional (meth)acrylate monomer having two or more (meth)acryloyl groups in the molecule can be used in combination with a monomer having one polymerizable unsaturated bond of (meth)acrylic acid ((meth)acryloyl group) in the molecule.
[0119] Of the difunctional or higher (meth)acrylate monomers, preferred examples of the difunctional (meth)acrylate monomer include neopentyl glycol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, tripropylene glycol di(meth)acrylate, ethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, hydroxypivalic acid neopentyl glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, and dicyclopentanyl di(meth)acrylate.
[0120] Among the difunctional or higher (meth)acrylate monomers, trifunctional or higher (meth)acrylate monomers include ECH (epichlorohydrin) modified glycerol tri(meth)acrylate, EO (ethylene oxide) modified glycerol tri(meth)acrylate, PO (propylene oxide) modified glycerol tri(meth)acrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, EO modified phosphoric acid triacrylate, trimethylolpropane tri(meth)acrylate, caprolactone modified trimethylolpropane tri(meth)acrylate, EO modified trimethylolpropane tri(meth)acrylate, and PO modified trimethylolpropane tri(meth)acrylate. Preferred examples of the acrylate include tris(acryloxyethyl)isocyanurate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol penta(meth)acrylate, caprolactone-modified dipentaerythritol hexa(meth)acrylate, dipentaerythritol hydroxypenta(meth)acrylate, alkyl-modified dipentaerythritol penta(meth)acrylate, dipentaerythritol poly(meth)acrylate, alkyl-modified dipentaerythritol tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol ethoxy tetra(meth)acrylate, and pentaerythritol tetra(meth)acrylate.
[0121] [Photopolymerization initiator] The photopolymerization initiator is not particularly limited as long as it is a compound capable of generating radicals upon irradiation with ultraviolet or visible light, and examples thereof include benzophenone-based, acetophenone-based, benzoin ether-based, and thioxanthone-based photopolymerization initiators.
[0122] Specific examples of photopolymerization initiators include benzophenone, Michler's ketone, 4,4'-bis(diethylamino)benzophenone, xanthone, thioxanthone, isopropyl xanthone, 2,4-diethylthioxanthone, 2-ethylanthraquinone, acetophenone, 2-hydroxy-2-methylpropiophenone, 2-hydroxy-2-methyl-4'-isopropylpropiophenone, 1-hydroxycyclohexyl phenyl ketone, isopropyl benzoin ether, isobutyl benzoin ether, 2,2-diethoxyacetophenone, 2,2-dimethylphenyl ketone ... 2-phenylacetophenone, camphorquinone, benzanthrone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1, 4-dimethylaminobenzoic acid ethyl, 4-dimethylaminobenzoic acid isoamyl, 4,4'-di(t-butylperoxycarbonyl)benzophenone, 3,4,4'-tri(t-butylperoxycarbonyl)benzophenone, 3,3',4,4'-tetra(t-butylperoxycarbonyl)benzo benzophenone, 3,3',4,4'-tetra(t-hexylperoxycarbonyl)benzophenone, 3,3'-di(methoxycarbonyl)-4,4'-di(t-butylperoxycarbonyl)benzophenone, 3,4'-di(methoxycarbonyl)-4,3'-di(t-butylperoxycarbonyl)benzophenone, 4,4'-di(methoxycarbonyl)-3,3'-di(t-butylperoxycarbonyl)benzophenone, 2-(4'-methoxystyryl)-4,6-bis(trichloromethyl)-s-triazine, 2-(3',4'-dimethoxystyryl) 2-(2',4'-dimethoxystyryl)-4,6-bis(trichloromethyl)-s-triazine, 2-(2'-methoxystyryl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4'-pentyloxystyryl)-4,6-bis(trichloromethyl)-s-triazine, 4-[pN,N-di(ethoxycarbonylmethyl)]-2,6-di(trichloromethyl)-s-triazine, 1,3-bis(trichloromethyl)-5-(2'-chlorophenyl)-s-triazine, 1,3-Bis(trichloromethyl)-5-(4'-methoxyphenyl)-s-triazine, 2-(p-dimethylaminostyryl)benzoxazole, 2-(p-dimethylaminostyryl)benzthiazole, 2-mercaptobenzothiazole, 3,3'-carbonylbis(7-diethylaminocoumarin), 2-(o-chlorophenyl)-4,4',5,5'-tetraphenyl-1,2'-biimidazole, 2,2'-bis(2-chlorophenyl)-4,4',5,5'-tetrakis(4-ethoxycarbonylphenyl)-1,2'-biimidazole, 2,2'-bis(2 ,4-dichlorophenyl)-4,4',5,5'-tetraphenyl-1,2'-biimidazole, 2,2'-bis(2,4-dibromophenyl)-4,4',5,5'-tetraphenyl-1,2'-biimidazole, 2,2'-bis(2,4,6-trichlorophenyl)-4,4',5,5'-tetraphenyl-1,2'-biimidazole, 3-(2-methyl-2-dimethylaminopropionyl)carbazole, 3,6-bis(2-methyl-2-morpholinopropionyl)-9-n-dodecylcarbazole, 1-hydroxycyclohexyl phenyl ketone, bis(η, 5 -2,4-cyclopentadien-1-yl)-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)-phenyl)titanium, 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and 2,4,6-trimethylbenzoyldiphenylphosphine oxide can be mentioned.
[0123] The content of the photopolymerization initiator is preferably 1 to 20 mass% of the total amount of the photocurable ink composition in order to obtain excellent photocurability against ultraviolet light, more preferably 2 to 15 mass%, and even more preferably 3 to 10 mass%.
[0124] [Other ingredients] Other components may be added to the photocurable ink composition within the range that does not impair the effects of the present invention. Examples of other components include polymerization inhibitors, fillers, pigments and dyes, and various coating additives (leveling, defoaming, viscosity adjustment).
[0125] [Uses of photocurable ink composition] Since the photocurable ink composition contains resin-coated wavelength conversion particles, it can be used in various applications that utilize the fluorescent properties, such as wavelength conversion members for displays, fluorescent printed matter, fluorescent labels, etc. In particular, it can be effectively used as an inkjet ink or offset ink for producing wavelength conversion members for partially converting blue light from a backlight into red light or green light.
[0126] In particular, when the photocurable ink composition is used for backlight, the viscosity of the photocurable ink composition of the ink-jet ink is preferably 1 to 100 mPa·s, and the viscosity of the photocurable ink composition of the offset ink is preferably 10 to 100 Pa·s.
[0127] <Method of producing resin-coated wavelength-converting particles> The above-mentioned resin-coated wavelength conversion particles can be suitably produced by the production method of the present invention. That is, the production method of the present invention is characterized by comprising a step of spraying, under light irradiation, a dispersion containing first coated particles in which wavelength conversion particles containing quantum dots or organic phosphors are coated with a first coating material containing a light-transmitting resin, an alicyclic epoxy compound, and a photoacid generator to obtain resin-coated wavelength conversion particles in which the alicyclic epoxy compound is cured (hereinafter referred to as the "spraying step").
[0128] The resin-coated wavelength conversion particles described above can also be produced by a method different from the production method of the present invention, for example by spraying a dispersion containing the first coated particles and an alicyclic epoxy compound and contacting it with an acidic solution to obtain resin-coated wavelength conversion particles in which the alicyclic epoxy compound is cured. The production method of the present invention will now be described.
[0129] [Preparation of first coated particles] Methods for producing first coated particles in which wavelength-converting particles containing quantum dots or organic phosphors are coated with a first coating material containing a light-transmitting resin include a method of dissolving the light-transmitting resin in a solvent and spraying a resin solution in which the wavelength-converting particles are dispersed, and drying and solidifying the solvent, and a method of finely pulverizing a mixture in which the wavelength-converting particles are dispersed in the light-transmitting resin. Any of the above-mentioned quantum dots, organic phosphors, light-transmitting resins, etc. can be used as raw materials.
[0130] The solvent may be any solvent that the light-transmitting resin can dissolve in. In the spray method, the resin concentration in the resin solution is preferably 10 to 30% by mass from the viewpoints of drying speed, viscosity, and the like.
[0131] In order to improve the dispersibility of the quantum dots or organic phosphors, it is possible to perform surface modification or add a dispersant or coupling agent. In addition, when using wavelength conversion particles dispersed in a solvent, it may be preferable to replace the solvent. For example, it may be preferable to replace the solvent of quantum dots dispersed in an aqueous solvent with an organic solvent.
[0132] [Spraying process] The amount of photoacid generator used in the spraying step is preferably 1 to 10% by mass, more preferably 1 to 5% by mass, from the viewpoint of obtaining dense resin-coated wavelength-converting particles while ensuring sufficient curability of the alicyclic epoxy compound. The dispersion in the spraying step can also contain a solvent, etc., if necessary.
[0133] The conditions for the light irradiation in the spraying step are sufficient as long as the alicyclic epoxy compound can be cured by spraying, and irradiation with ultraviolet rays is preferred from the viewpoint of the curing speed. It is also possible to increase the residence time of the sprayed particles by generating an air flow.
[0134] The coated wavelength-converting particles obtained by spraying may be subjected to treatments such as post-curing, classification, surface treatment, and crushing. EXAMPLES
[0135] The present invention will be described in detail below using examples, but the present invention is not limited to the following examples as long as it does not deviate from the gist of the present invention. The evaluation items in the examples were measured as follows.
[0136] (1) Measurement of fluorescence spectrum The evaluation pellets were hardened to prepare measurement samples with a size of Φ1 mm, and the fluorescence spectrum was measured using a fluorescence spectrophotometer (RF-5300PC, manufactured by Shimadzu Corporation).
[0137] (2) Evaluation of durability against blue light The pellets for evaluation were left for six months under a floodlight (at a distance of 30 cm) using a blue LED with a dominant light of 450 nm and a power consumption of 20 W, and the maintenance of luminescence after six months was visually examined. For pellets whose luminescence disappeared quickly, the number of days it took for the luminescence to disappear was evaluated.
[0138] (3) Measurement of particle size The particles were ultrasonically dispersed in a solvent (xylene) at a concentration of 0.05% by mass, and the particle size distribution was measured using a dynamic light scattering particle size distribution analyzer (Microtrack Bell Co., Ltd., UPA-EX150). The average particle size was determined as the volume-based median size (median size, particle size at which the cumulative frequency is 50%, D 50 ) was calculated.
[0139] Example 1 (QD / PMMA / THI-DE / TMP-A) In a container, 5 g of acrylic resin (PMMA pellets, manufactured by Mitsubishi Chemical Corporation) was dissolved in 100 ml of acetone to prepare a resin solution. 7 ml of InP / ZnS quantum dots (semiconductor quantum dots, manufactured by GS Alliance Co., Ltd., solvent: toluene, solid content 5% by mass) were added to this resin solution, and sprayed into an inert gas (N2) heated to 70°C to microparticle the dots to an average particle size of 25 nm, thereby obtaining first coated particles consisting of quantum dots coated with a first coating material (acrylic resin).
[0140] 60% by mass of an alicyclic epoxy compound (Epocalic THI-DE (registered trademark) manufactured by ENEOS Corporation) was mixed with 5% by mass of a sulfonium salt-based photocationic polymerization initiator (CPI-100P manufactured by San-Apro Co., Ltd.) and 35% by mass of the first coated particles, and the mixture was sprayed into a space irradiated with a 1.5 kW metal halide lamp (wavelength 405 nm) to obtain resin-coated wavelength conversion particles coated with a second coating material (alicyclic epoxy resin). The particle size at this time was 30 nm to 40 nm (average particle size D 50 =35 nm). The solid contents in the resin-coated wavelength conversion particles were: wavelength conversion particles 2 mass %, the first coating material 34 mass %, and the second coating material 64 mass %.
[0141] The obtained resin-coated wavelength-converting particles were used to prepare a UV ink, which was prepared by mixing 75% by mass of an acrylate (Light Acrylate TMP-A: trimethylolpropane triacrylate, manufactured by Kyoei Chemical Industry Co., Ltd.) which is a radical polymerizable compound, with 5% by mass of a phosphine oxide-based photopolymerization initiator (Omnirad 819: phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, manufactured by IGM Resins BV) in a container, and adding 20% by mass of the resin-coated wavelength-converting particles to prepare a UV ink.
[0142] The obtained UV ink was placed in a silicone mold for preparing pellets for evaluation and polymerized with light from a 1.5 kW metal halide lamp (wavelength 405 nm) to prepare pellets for evaluation (plate-like, 10 mm thick). The content of resin-coated wavelength-converting particles in the pellets for evaluation (in the solid content) was 20 mass %.
[0143] The materials used above, their contents, etc. are shown in Table 1. Table 1 also shows the results of evaluating blue light durability and measuring the fluorescence spectrum using this evaluation pellet. As a result, it was confirmed that the quantum dot light emission was maintained at 97% or more after being left for 6 months. Furthermore, the peak wavelength of the emission of the evaluation pellet in response to excitation light (wavelength 450 nm) was 650 nm, and the half-value width was 40 nm.
[0144] Example 2 (OF / PMMA / THI-DE / TMP-A) Resin-coated wavelength conversion particles were prepared under the same conditions as in Example 1, except that 4 g of organic phosphor OF (manufactured by Tokyo Chemical Industry Co., Ltd., bromopyrogallol red, average particle size 50 nm) was used instead of the quantum dots in Example 1, as shown in Table 1. Evaluation pellets were made using UV ink and the durability to blue light was evaluated. As a result, it was confirmed that the particles had the fluorescent properties shown in Table 1, and that the organic phosphor maintained 90% or more of its emission after being left for 6 months.
[0145] Example 3 (QD / PSt / THI-DE / TMP-A) Resin-coated wavelength conversion particles were prepared under the same conditions as in Example 1, except that 5 g of polystyrene resin PS (GPSS, manufactured by Toyo Engineering Corporation) was used instead of the acrylic resin in Example 1, as shown in Table 1. Evaluation pellets were made using UV ink and the durability to blue light was evaluated. As a result, it was confirmed that the particles had the fluorescent properties shown in Table 1, and that the quantum dots maintained 97% or more of their emission after being left for 6 months.
[0146] Example 4 (QD / PMMA / DE-103 / TMP-A) Resin-coated wavelength conversion particles were prepared under the same conditions as in Example 1, except that the same amount of alicyclic epoxy compound (Epocalic DE-103 (registered trademark), manufactured by ENEOS Corporation) was used as in Example 1, as shown in Table 1, and evaluation pellets were made using UV ink to evaluate the durability to blue light. As a result, it was confirmed that the particles had the fluorescent properties shown in Table 1, and that the quantum dots maintained 97% or more of their emission after being left for 6 months.
[0147] <Comparative example 1> (QD / PMMA / TMP-A) Resin-coated wavelength-converting particles were prepared under the same conditions as in Example 1, except that no second coating material was provided, and evaluation pellets were made from UV ink to evaluate blue light durability, as shown in Table 1. As a result, as shown in Table 1, light emission was no longer observed within three days.
[0148] <Comparative example 2> (QD / THI-DE / TMP-A) Resin-coated wavelength conversion particles were prepared under the same conditions as in Example 1, except that the first coating material was not provided, and evaluation pellets were made from UV ink to evaluate the durability to blue light, as shown in Table 1. As a result, as shown in Table 1, light emission was no longer observed within one day.
[0149] <Comparative example 3> (QD / PVA / THI-DE / TMP-A) Resin-coated wavelength-converting particles were prepared under the same conditions as in Example 1, except that the same amount of polyvinyl alcohol resin PVA (Exceval, manufactured by Kuraray Co., Ltd.) was used instead of the acrylic resin in Example 1, as shown in Table 1. Evaluation pellets were made using UV ink and durability to blue light was evaluated. As a result, as shown in Table 1, light emission could no longer be confirmed after 7 days.
[0150] Comparative Example 4 (QD / PMMA / GE / TMP-A) Resin-coated wavelength-converting particles were prepared under the same conditions as in Example 1, except that instead of using the alicyclic epoxy compound in Example 1, the same amount of glycidyl-type epoxy compound GE (Epolite 40E: ethylene glycol diglycidyl ether, manufactured by Kyoeisha Chemical Co., Ltd.) was used, as shown in Table 1. Evaluation pellets were made from UV ink and durability to blue light was evaluated. As a result, as shown in Table 1, light emission could no longer be confirmed after 20 days.
[0151] <Comparative example 5> (OF / THI-DE / TMP-A) Resin-coated wavelength-converting particles were prepared under the same conditions as in Example 1, except that 4 g of organic phosphor OF (Bromopyrogallol Red, average particle size 50 nm, manufactured by Tokyo Chemical Industry Co., Ltd.) was used instead of the quantum dots in Example 1, and the first coating material was not provided, as shown in Table 1. Evaluation pellets were then made from UV ink to evaluate the durability to blue light. As a result, as shown in Table 1, light emission could no longer be confirmed within one day.
[0152]
Table 1
Claims
1. wavelength-converting particles including quantum dots or organic phosphors; a first coating material that coats the wavelength converting particles and contains a light-transmitting resin; a second coating material that coats the first coating material and contains a cured product of an alicyclic epoxy compound; 4. A resin-coated wavelength-converting particle comprising:
2. 2. The resin-coated wavelength conversion particle according to claim 1, wherein the alicyclic epoxy compound comprises one or more aliphatic rings and one or more oxygen atoms directly bonded thereto.
3. 3. The resin-coated wavelength conversion particle according to claim 1, wherein the light-transmitting resin is a (meth)acrylic resin, a polycarbonate resin, a polystyrene resin, or a polyolefin resin.
4. 4. The resin-coated wavelength-converting particle according to claim 1, wherein the wavelength-converting particle has an emission wavelength in the range of 500 to 580 nm or 600 to 680 nm.
5. A resin-coated wavelength conversion particle according to any one of claims 1 to 4, A radical polymerizable compound, A photopolymerization initiator; A photocurable ink composition comprising:
6. A method for producing resin-coated wavelength-conversion particles, comprising the steps of: spraying, under light irradiation, a dispersion containing first coated particles in which wavelength-conversion particles containing quantum dots or organic phosphors are coated with a first coating material containing a light-transmitting resin, an alicyclic epoxy compound, and a photoacid generator, to obtain resin-coated wavelength-conversion particles in which the alicyclic epoxy compound is cured.
Citation Information
Patent Citations
Pigment dispersion, UV-curable inkjet ink precursor, inkjet recording method, printed matter and manufacturing process of the pigment dispersion
JP2005132874A
Wavelength conversion member, backlight unit, liquid crystal display device, and polymerizable composition containing quantum dot
JP2017062458A
Graphene quantum dot-polymer composites and their fabrication methods
JP2017525781A
Ink composition and method for producing the same, photoconversion layer and color filter
JP2018193525A
Ink composition, light conversion layer, and color filter
JP2019086745A